Respuesta :

Answer:

The reduced expression is:  

[tex]\frac{3\,y\,z^4}{\,x^2}[/tex]

Step-by-step explanation:

Start by cancelling out common factors in numerator and denominator (including the "-1" factor present in both):

[tex]\frac{-36\,x^4\,y^4\,z^5}{-12\,x^6\,y^3\,z} = \frac{3\,x^4\,y^4\,z^5}{\,x^6\,y^3\,z} =\frac{3\,y^4\,z^5}{\,x^2\,y^3\,z} =\frac{3\,y\,z^5}{\,x^2\,z} =\frac{3\,y\,z^4}{\,x^2}[/tex]

where we did cancellations of first numerical factors, and then the variables addressing one at a time.

ACCESS MORE